The Effect of Product Quality and Service Quality on Consumer Satisfaction at Roya Café Mantingan - Tussifah, Hamidah; Navitsha, Nadila Putri (Universitas Islam Negeri Sunan Kudus, 2021)
Quality assurance becomes the main priority for the company. The quality of the product is closely related to the ability of the product to carry out its functions, with the good quality of the product will make the consumers satisfied and trust. Customer satisfaction is something that needs to be considered by the company. Another factor that can affect customer satisfaction is the quality of service as an effort to fulfill the needs and desires of consumers and the provision of delivery in keeping up with consumer expectations. This study aims to determine the influence of product quality and service quality partially and simultaneously on customer satisfaction at Roya Café. The research method uses a type of quantitative research. Data collection techniques are carried out by observation. The research instrument uses questionnaires distributed to Roya Café consumers. The sample was taken by 226 respondents, using Non-Probability Sampling technique with Incidental Sampling approach. The analysis techniques in this study used multiple linear regressions. The results showed that partially the quality of the product had a positive and significant effect on customer satisfaction and the quality of service partially influenced positively and significantly to customer satisfaction at Roya Café.